2018
DOI: 10.2524/jtappij.72.944
|View full text |Cite
|
Sign up to set email alerts
|

Kraft Cooking and Bleaching Ability of Lowdensity Acacia Wood and Hardwoods with Varying Chemical Characteristics of Lignin

Abstract: Low-density acacia(Acacia hybrid)wood chips, relatively high-density acacia(Acacia mearnsii)wood chips, eucalyptus(Eucalyptus globulus)wood chips, and Japanese mixed hardwood chips were cooked through a kraft cooking process using the continuous conventional mill digester. Chemical composition of these wood chips and properties of the obtained pulps were compared. Low-density acacia wood chips showed the highest lignin content, the lowest combined yield of syringaldehyde and vanillin obtained by alkaline nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This result is very low, as compared with the wood density of acacias. 20 Tanifuji et al 21 showed that the wood density of the Acacia hybrid is lower than that of other acacias. Low wood density results in lower pulp yield.…”
Section: Resultsmentioning
confidence: 99%
“…This result is very low, as compared with the wood density of acacias. 20 Tanifuji et al 21 showed that the wood density of the Acacia hybrid is lower than that of other acacias. Low wood density results in lower pulp yield.…”
Section: Resultsmentioning
confidence: 99%